STUDY OF THE POTENTIAL USE OF THE OXBOW AS A SOURCE OF RAW WATER (CASE STUDY OF CIUJUNG LAMA OXBOW, SERANG REGENCY) - Linati, Rifqi
Ciujung Oxbow is a segment of the former river from the results of the Ciujung River. In this study, we will discuss the performance of dead rivers on their use as a source of raw water. To find the value of the reliability of dead rivers in meeting the needs of raw water around the study site, a hydrological function is needed to get a runoff rain model in this case using the sacramento method. After getting the value of water availability and analyzing the water demand, a reservoir is simulated to assess the success of the dead river operation. Water use simulation conducted in 2007 untill 2017 as an evaluation to assess the success of storage operations, using three discharge conditions namely wet conditions, normal conditions and dry conditions. In this study the simulation uses two scenarios, namely the inflow scenario without the supply with the inflow scenario with the supply. The simulation results in the first scenario of reservoir operation without supply from the main river, with the level of meeting water needs in 37% wet conditions, 18% normal conditions and 10% dry conditions. The second scenario of reservoir operation simulation with the supply of the main river, with the level of fulfillment of raw water requirements in the three discharge conditions can be increased to 100% with the use of pumps in wet conditions of 0.15 m3/sec which are operated from August to October and 0.18 m3/sec in November to April, normal conditions of 0.15 m3/sec in August, September and 0.2 m3/sec in October to April, dry conditions of 0.15 m3/sec in In June, July and 0.18 m3/sec in August to April.